2012
DOI: 10.1371/journal.pone.0052333
|View full text |Cite
|
Sign up to set email alerts
|

Upregulating Noxa by ER Stress, Celastrol Exerts Synergistic Anti-Cancer Activity in Combination with ABT-737 in Human Hepatocellular Carcinoma Cells

Abstract: The human hepatocellular carcinoma (HCC) represents biologically aggressive and chemo-resistant cancers. Owing to the low affinity with the apoptotic factor Mcl-1, the BH3 mimetic drug ABT-737 failed to exert potent cancer-killing activities in variety of cancer models including HCC. The current study demonstrated that combining ABT-737 and Celastrol synergistically suppressed HCC cell proliferation, and induced apoptosis which was accompanied with the activation of caspase cascade and release of cytochrome c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 38 publications
(49 reference statements)
6
37
0
Order By: Relevance
“…Immunoblot analysis of whole cell lysates further demonstrated celastrol treatment reduced the pro-form of caspase 9 and led to the accumulation of active caspase 3 (Fig. 3B), consistent with the observations of others [3436]. Increased accumulation of pro-apoptotic BAK was also observed following celastrol treatment (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Immunoblot analysis of whole cell lysates further demonstrated celastrol treatment reduced the pro-form of caspase 9 and led to the accumulation of active caspase 3 (Fig. 3B), consistent with the observations of others [3436]. Increased accumulation of pro-apoptotic BAK was also observed following celastrol treatment (Fig.…”
Section: Resultssupporting
confidence: 90%
“…These data confirm a role for the intrinsic (mitochondrial) apoptotic pathway in celastrol-mediated cancer cell death and extend previous observations that it can induce apoptosis in cultured cells [29,34,37]. The ability of celastrol to induce ubiquitination (Ub) in whole cell lysates has been reported in different cancer subtypes [20,36,37]. Immunoblot analysis revealed that celastrol-resistant cell lines (CAL27 and FaDu) accumulated Ub proteins much more slowly than celastrol-sensitive UMSCC23 cells (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Although several reports mentioned about the involvement of celastrol in apoptosis of hepatoma cells, no study has been reported the anti-metastatic function of celastrol in HCC [25,26]. In this study, we investigated the effect of celastrol on migration and invasion ability of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, Zhu et al 57 showed previously that celastrol activates the ER-stress response in human hepatocellular carcinoma cells via a mechanism that is dependent on preserved eIF2 α -ATF4-Noxa signaling. In line with these results, celastrol induces cytoplasmic vacuolation in several human cancer cell lines in conjunction with elevated membrane-bound LC3 (LC3-II).…”
Section: Discussionmentioning
confidence: 99%